PENGARUH KOMPOSISI MEDIA TANAM DAN JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG UNGU (Solanum melongena L.) - Kiki Dita Ayu Ninda Sari; Juli Santoso; Nora Augustien Kusumaningrum (UPN VETERAN JAWA TIMUR, 2021)
Eggplant (Solanum melongena L.) is a horticultural plant that has been cultivated for a long time both in the yard or in the cultivation land to use their fruit. This study aims to know the composition of the growing media and types of manure toward growth and yield of purple eggplant var. Antaboga. The study was conducted from February to May 2020 in Pabean Village, Sedati District, Sidoarjo, East Java. The reaserch were arranged in Completely Randomized Design with two factors and three duplications. The first factor was the composition of the growing media (M) on the three level : M1 = soil : organic fertilizer (1:0), M2 = soil : organic fertilizer (1:1), M3 = soil : organic fertilizer (1:2) and M4 = soil : organic fertilizer (2:1), the second factor was to type of manure (P) on the three level: P1 = chicken manure, P2 = cow manure and P3 = goat manure. The results showed that there was an interaction between the composition of the planting medium and the type of manure on plant height, number of leaves, total number of flowers planted, total number of fruits planted, total fruit weight and fruit length. The best results were obtained from the combination treatment of the composition of the growing media (1: 2) and cow manure (M2P2).